Oxford starter Spanish dictionary - edited by Ana Cristina Llompart; Jane Horwood; Carol Styles Carvajal (Oxford University Press, 2003)
The Oxford Starter Spanish Dictionary is a unique, friendly approach to learning Spanish. Specially designed for beginners, this volume covers everyday vocabulary and core survival phrases. From irregular verb forms to common idiomatic usage, it provides generous coverage of the Spanish language. It provides detailed guidance, correct grammar, the best translation, thematic boxes, and symbols, and it includes no abbreviations, making this dictionary especially easy to understand. These innovative teaching tools make this dictionary an unparalleled introduction to the Spanish language